Penyerapan Tenaga Kerja Dan Indeks Pembangunan Manusia Terhadap Upah Minimum Di Indonesia - Bambang Sujagad Susanto (The Asia Pacific Journal Of Management Studies, 2014)
This study aims to examine and analyze the effect of labor absorption and human development index on provincial minimum wage in five provinces of Indonesia. Data used a panel data which combines the data time series and cross section data. The method used is pooled least squares method is analyzed by software Eviews 7. The results showed that the effect of labor absorption on provincial minimum wage were negative, so if there is an increase in labor absorption, it will cause a decrease in the provincial minimum wage and improvement of the human development index will have an impact also on the increase in the provincial minimum wage.